Delivering justice: a holistic and multidisciplinary approach ; Liber Amicorum in honour of Christopher Hodges - Kramer, Xandra Ellen; Voet, Stefaan; Ködderitzsch, Lorenz; Tulibacka, Magdalena; Hess, Burkhard (Hart, 2022)
"In this Liber Amicorum, leading experts and old-time friends from around the world come together to pay tribute to Christopher Hodges' multifaceted career and work by exploring what can be done to deliver justice and fairness, focusing on collective redress, consumer dispute resolution, court system reform, ethical business regulation and regulatory delivery. After a decade-long career as a solicitor, Christopher Hodges became Professor of Justice Systems at the Centre for Socio-Legal Studies at the University of Oxford. Throughout his academic career he worked on a variety of topics dealing with access to justice and dispute resolution: from product liability, procedural/funding systems and collective redress, to alternative dispute resolution and ethical business regulation. In 2021 Christopher Hodges was awarded an OBE for services to business and law. His ground-breaking research not only inspired students and colleagues, but also influenced policymakers worldwide. Delivering justice, and "making things better", runs like a thread through his work; the same thread connects the chapters in this book"--